The Level of Awareness on the Antibacterial Therapy Among Adults in Cablong Sta. Barbara Residents - Pajalla, Nicolyn; Unating, Jennifer; Collado, Leslie Ann; Beltran-Villar, Johanna (MALATA SAINS INDONESIA, 2025)
Introduction: Research in Antibacterial Therapy is vital due to its ability to combat infectious diseases effectively. This medicine was impacted on the world particularly in the public health. Inappropriate or improper antibiotic use contributes significantly to the development and spread of antibiotic-resistant bacteria. To safeguard the future, it must continue to invest in research to combat antibiotic resistance and ensure the efficacy of antibiotics for generations to come. Objective: The time to act is now, for the consequences of inaction are too alarming to contemplate. Hence, the researchers conducted this study to assess the level of awareness of antibacterial therapy among adults. Method: The research design that was used in this study was descriptive and the setting was in a rural area, where it is characterized by its limited access to healthcare facilities providing a suitable setting, to investigate insights into how Antibiotic resistance manifests in undeserved and distant communities. The respondents consist of 50 adults and research sampling that was used in this study was purposive. Result: The results revealed that the majority of the respondents are least aware in terms of the Antibacterial therapy. These adults were evaluated concerning their level of awareness and knowledge about the antibacterial therapy. Furthermore, the respondents are not fully aware of the Antibacterial Therapy. Some of them buy antibiotics without a doctor's prescription and ask for antibiotics from their friends, family, and relatives. They are not also highly aware of the consequences of antibiotic use, such as long hospital days, higher medical costs, and antibiotic resistance. Conclusion: Findings also showed that there is a significant relationship between higher educational attainment and the category of use and misuse of Antibacterial therapy.